Hubungan antara Prostatitis Kronis dan Gangguan Reproduksi Pria: Tinjauan Literatur Terkini - Surya Putra, Abdul Hafiidh; Suryoadji, Kemal Akbar; Achmadsyah, Armand; Birowo, Ponco (Griya Widya: Journal of Sexual and Reproductive Health, 2025)
Background: This literature review aims to present the latest scientific findings that explain the relationship between chronic prostatitis and male reproductive disorders. Method: This study was a narrative literature review that identified articles from PubMed, Scopus, and Google Scholar using the keywords "chronic prostatitis", "CP/CPPS", "male infertility", "erectile dysfunction", and "ejaculatory dysfunction". Inclusion criteria include publications in the last 10 years that discuss the association between chronic prostatitis and male reproductive disorders. The data were analyzed descriptively to identify patterns of interdependence. Results: Data synthesis showed that chronic prostatitis was associated with a significant decrease in sperm concentration, motility, morphology, and viability. Patients also had a threefold risk of erectile dysfunction, as well as a high prevalence of painful ejaculation (30–65%) and premature ejaculation (±40%). Inflammatory mechanisms and oxidative stress have been shown to play an important role in pathogenesis, while multimodal therapies, including antibiotics, antioxidants, PDE5 inhibitors, phytotherapy, and pelvic floor physiotherapy, show better effectiveness than monotherapy. Implications: These results confirm the need to evaluate the reproductive aspect in patients with chronic prostatitis, as well as a multidisciplinary approach to improve quality of life and fertility. Novelty: This study presents an up-to-date comprehensive review that integrates clinical evidence, pathophysiology, and therapeutic strategies, thereby enriching understanding and supporting the development of more effective management.